Dispersion and Personal Reception of Particulate Matter Generated by Burning Incense - Kengchuwong , Metta; Sanghaw, Ratikorn; Kanchak, Angsuma; Rattanadon, Butsayamat; Trisupakitti, Somsuk; Morris, John (Journal of Food Health and Bioenvironmental Science, 2023)
We studied the amount of particulate matter dispersed in the air and received by a person and the heat index from incense burning in a room with and without ventilation and to study the relationship of each size of dust diffusion in the air from incense burning in a room with and without ventilation. Total concentrations of dust dispersed in the air was measured, for 10  and 2.5  particles, with a personal air sampler and the heat index was measured with a heat stress monitor. Two rooms were studied: one small (4x8x2.6 m3) and one larger (8x8x2.6 m3). Common incense and a smokeless version were tested. Particulate matter and heat index was measured every 10 min over an 8 hour day. A sampler attached to a mannequin in the room estimated exposure by a person working in the room, so that TPM received by a person was measured continuously for 8 hours. (i) Every condition of the room studied did not exceed the TPM criteria specified by the Department of Health; (ii) TPM exposure by a person in an unventilated room was higher than that in a ventilated room; (iii) heat index measurements showed that incense burning alone was insufficient to significantly affect people in a 50 m3 space (iv) persons exposed to high TAM concentrations are also likely to be exposed to high levels of PM10 and PM2.5. However, TPM, PM10 and PM2.5 concentrations from incense burning were sufficiently well correlated that any one measurement would reasonably well predict the other two.